Metformin decreases testicular damages following ischaemia/reperfusion injury in rats - Saribal, Devrim; Erdem, Erkan; Gungor-Ordueri, Nazli Ece; Usta, Akin; Karakus, Cemil; Karacan, Meric (Wiley, 2020)
The effects of metformin on a testicular torsion injury in adolescent rat testis after I/R were evaluated in the present study. Forty adolescent rats were divided into five groups with eight rats per group: a control group; a sham-operated group; an ischaemia group, where torsion was applied for 4 hr and testis was examined immediately after detorsion; an I/R group, where torsion was applied for 4 hr and the testis was examined 4 hr after detorsion; and an I/R + M group, where the metformin (300 mg/kg) administration was added to the identical procedures used for the I/R group. Spermatogenesis, basal membrane integrity and cleaved caspase-3 expression were assessed. The I/R + M group had a significantly higher Johnsen score than the I/R group (7.9 +/- 0.1 vs. 7.5 +/- 0.2; p F-value = 14.2). Failure of basal membrane integrity was highest in the ischaemia group (45 +/- 5) compared to the other groups (control group, 20 +/- 5; sham-operated group, 16.6 +/- 2.8), but not different between the I/R + M (31.6 +/- 12.5) and the I/R groups (25 +/- 3.5). Cleaved caspase-3 expression was highest in the ischaemia group (73.5 +/- 0.7), and significantly lower in the I/R + M group (33.4 +/- 0.9) than the I/R group (58.5 +/- 0.2; p F-value = 7.6). Metformin decreases testicular damage by exerting protection against the harmful effects of I/R on spermatogenesis and alleviating apoptosis in adolescent rat testis.
Keywords: Apoptosis; Cleaved Caspase-3; Metformin; Testicular İschaemia; Reperfusion; Torsion; Detorsion; Activated Protein-Kinase; Ischemia-Reperfusion Injury; Torsion-Detorsion Injury; Cell-Specific Apoptosis; Ischemia/Reperfusion Injury; Oxidative Stress; Tissue; Ampk